Analysis of the Effect of the Use of Sudetan Pipe Tunnels on the Water Level of the Ciliwung River and Cipinang River, East Jakarta - Nurdyansyah, Haris; Desy, Natsar; Gusty, Sri (Universitas Ibn Khaldun Bogor, 2025)
Ciliwung River is one of the 13 major rivers in Jakarta that causes flooding, especially in the East Jakarta area. In an effort to reduce flooding along the Ciliwung River in the DKI Jakarta area, efforts were made to divert part of the Ciliwung River flow during floods to the East Flood Canal channel through the construction of a double pipe tunnel commonly called a sudetan in the Bidara Cina Village area, where the tunnel also passes through the Cipinang River as a diversion of discharge from the Cilwung River. The purpose of this study is to determine the effect of the sudetan pipe tunnel on the water level of Ciliwung River and Cipinang River. In this study, we will model the water level of Ciliwung River and Cipinang River to see the diversion of discharge into the sudetan pipe tunnel to reduce the overflow of water around Ciliwung River and Cipinang River. The method of this research is done by quantitative descriptive method to the value of water level in Ciliwung River and Cipinang River before the sudetan tunnel and after the sudetan tunnel and looking for comparison by using rating curve. The results of this study are based on the modeling analysis of the maximum flood discharge that can be accommodated by the ciliwung river before the existence of the sewer pipe tunnel in Q1 of 323 m3 / s there is an increase after the sewer pipe tunnel which is 539 m3 / s. It can be seen that the use of a sewer pipe tunnel can reduce the flood water level by 4 meters. It can be seen that the use of tunnel pipes can reduce the elevation of flood water up to 4 meters. Obtained for the ciliwung discharge of the return period Q1=323 m3/det Q2=377.66 m3/det Q5=433 m3/det Q10=462.45 Q25=493.52 m3/det Q50=518.83 m3/det Q100=539.62 m3/det.